SISTEM BAGI HASIL KEBUN AREN DALAM PERSPEKTIF EKONOMI SYARIAH DI NAGARI ANDALEH BARUH BUKIK KECAMATAN SUNGAYANG KABUPATEN TANAH DATAR - Himyar Pasrizal; Rahmat Firdaus; Mirawati Mirawati (UIN Mahmud Yunus Batusangkar, 2021)
From the research conducted by the author in the field, it can be concluded that the distribution system for the palm plantation in Nagari Andaleh Baruh Bukik consists of the first three types of profit sharing with a ratio of 50%: 50%, a system of help, and a system of profit sharing with a ratio of 70%. : 30%. Profit sharing is carried out between the owner and cultivator of the palm plantation in Nagari Andaleh Baruh Bukik which has been mutually agreed to contain gharar and there is injustice in the distribution of the results from the palm tree (enau). Should every yield obtained from the palm tree (enau) cultivators must explain in detail to the owner about the results obtained. Every result obtained by the owner is also entitled to get results, such as selling fruit tabs, selling palm fibers, selling leaves and sticks of palm branches, and selling palm stems. So that the occurrence of an action that has taken the rights of others in the form of unfair distribution of results. This is evident when the distribution of the yield from the palm plantation often occurs problems caused by inconsistencies with what was agreed at the beginning with the results obtained between the cultivator and the owner.Keywords: System, profit sharing, Sharia economy